Cardio-Pulmonary Sequelae in Recovered COVID-19 Patients: Considerations for Primary Care. (June 2021) - Sarfraz, Zouina; Sarfraz, Azza; Barrios, Alanna; Garimella, Radhika; Dominari, Asimina; KC, Manish; Pandav, Krunal; Pantoja, Juan C.; Retnakumar, Varadha; Cherrez-Ojeda, Ivan
Background: Current literature lacks characterization of the post-recovery sequelae among COVID-19 patients. This review characterizes the course of clinical, laboratory, radiological findings during the primary infection period, and the complications post-recovery. Primary care findings are presented for long-COVID care. Methods: Adhering to PRISMA guidelines, 4 databases were searched (PubMed, Embase, CINAHL Plus, Scopus) through December 5, 2020, using the keywords "COVID-19 and/or recovered and/or cardiovascular and/or long-term and/or sequelae and/or sub-acute and/or complication." We included published peer-reviewed case reports, case series, and cross-sectional studies providing the clinical course of COVID-19 infection, and cardiopulmonary complications of patients who recovered from COVID-19, while making healthcare considerations for primary care workers. Results: We identified 29 studies across 9 countries including 37.9% Chinese and 24.1% U.S. studies, comprising 655 patients (Mean Age = 45) with various ethnical backgrounds including Asian and European. Based on the WHO COVID-19 severity classification scale, initial disease severity was mild for 377 patients and severe for 52 patients. Treatments during primary infection included corticosteroids, oxygen support, and antivirals. The mean value (in days) for complication onset after acute recovery was 28 days. Complete blood counts and RT-PCR tests were the most common laboratory results described. In 22 of the studies, patients showed signs of clinical improvement and were prescribed medications such as anticoagulants or corticosteroids. Conclusion: Post-recovery infectious complications are common in long-COVID-19 patients ranging from mild infections to life-threatening conditions. International thoracic and cardiovascular societies need to develop guidelines for patients recovering from COVID-19 pneumonia, while focused patient care by the primary care physician is crucial to curb preventable adverse events. Recommendations for real-time and lab-quality diagnostic tests are warranted to establish point-of-care testing, detect early complications, and provide timely treatment.